The antifungal activity of Glycosmis calcicola and G. rupestris extracts - Rahmani, Mawardi; Chew, Yean Ling; Meon, Sariah; Mohd Ismail, Hazar Bebe; Sukari, Mohd Aspollah (Taylor & Francis, 2004)
The antifungal activity of Glycosmis calcicola B.C. Stone and G. rupestris extracts was evaluated using poison food and spore germination techniques. The CHCl3 extract of G. calcicola has been shown to be most effective in inhibiting mycelial growth, sporulation, and spore germination on three fungal pathogens of chili. The antifungal compounds were identified as flindersine and desmethoxyanthophylline and their structures were determined by spectroscopic methods and comparison with reported data.